G403(P) Moodsey: developing a thematic real-time staff morale tracking model. (25th October 2020) - Daniels, R; Bhatt, R; Bulmer, S; Nousheh-Moore, A; Jones, V
Abstract : Aims: To develop a method of continuous assessment of subjective staff morale reporting and use the reporting data to inform improvements to staff wellbeing. Methods: A system, entitled MOODSEY, was developed asking multidisciplinary staff in a busy urban paediatric unit to anonymously retrospectively rate each shift as a 'Good Day' or 'Bad Day' at its conclusion. Broad demographic information was collected to aid with subgroup analysis. 'Complete' data required all 4 fields completed. This data was aggregated, and a score was plotted on a run chart. Prior to data collection, a listening exercise occurred to generate themes that staff reported as affecting their shifts. When reporting, staff were encouraged to signal which of these themes had led to their choice. These themes were aggregated and analysed using the Model for Improvement to inspire changes that would improve future scores & the frequency of themes being reporting. Paper and digital reporting techniques were designed to be minimally time-consuming and local champions encouraged reporting Results: The unit average MOODSEY score was plotted on a scale of -1 to +1 plotted on a run chart. In the first 2 months of reporting, a median score of 0.7 with statistically appropriate variability was found. Statistically significant shifts were seen for both positive and negative reporting. Thematic data showed that negative reporting was most commonly associated with Poor Staffing, Incivility and Unsupportive Seniors whilst positive reporting was associated with a Good Atmosphere, Good Teamwork and Supportive Seniors. 885 responses were collected in total (mean: 12.5 responses/day). The presence of champions on shift improved response rate for all roles. 66% of reporting cards were completed fully. Conclusion: The MOODSEY system has proven the concept of 'smart real-time monitoring of staff morale'. Thematic analysis correlates with existing findings in the literature. Further iterations are required to integrate the project into the department however the encouraging initial success gives a platform for ongoing assessment of work aimed at staff wellbeing.